2013
DOI: 10.1002/cctc.201300821
|View full text |Cite
|
Sign up to set email alerts
|

Platinum N‐Heterocyclic Carbene Nanoparticles as New and Effective Catalysts for the Selective Hydrogenation of Nitroaromatics

Abstract: Dedicated to Professor Ernesto Carmona on the occasion of his 65 th birthday.Abstract: In this communication, we report the first synthesis of Pt NPs stabilized with NHC ligands and their investigation as catalysts in the chemoselective hydrogenation of nitroarenes. The results in catalysis show that by a proper choice of the NHC stabilizer and the adjustment of the NHC/metal ratio, these NHC-capped Pt NPs exhibit high levels of activity and selectivity in the hydrogenation reactions. In particular, Pt NPs sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 49 publications
(23 reference statements)
2
60
0
1
Order By: Relevance
“…Ti NPs [138], and the use of carbene ligands to control the size of Pt [139] or Ru NPs [87,[140]. Weakly coordinating alcohols [141], [142] or carbohydrates like cyclodextrines [143] can also serve as stabilizers, as well as some solvents such as organic carbonates [144], ionic liquids [145], [146], [147], [148], or polyols [149], [150].…”
Section: Influence Of Ligand Coordination At the Surface Of Metal Nanmentioning
confidence: 99%
“…Ti NPs [138], and the use of carbene ligands to control the size of Pt [139] or Ru NPs [87,[140]. Weakly coordinating alcohols [141], [142] or carbohydrates like cyclodextrines [143] can also serve as stabilizers, as well as some solvents such as organic carbonates [144], ionic liquids [145], [146], [147], [148], or polyols [149], [150].…”
Section: Influence Of Ligand Coordination At the Surface Of Metal Nanmentioning
confidence: 99%
“…The strategy presented herein uses sulfonated N-heterocyclic carbene (NHC) ligands to stabilize platinum nanoparticles (PtNPs) in water, under air, for an indefinite time period. [4][5][6][7][8][9][10][11][12][13] Some of us have characterized the coordination of such ligands to ruthenium nanoparticles by solid-state NMR spectroscopy. Solidstate NMR studies showed coordination of the carbene ligands to the nanoparticle surface and allowed the determination of a 13 C-195 Pt coupling constant for the first time in a nanosystem (940 Hz).…”
mentioning
confidence: 99%
“…[1] The agglomeration of MNPs can be avoided by coordinating ligands to their surface. [4][5][6][7][8][9][10][11][12][13] Some of us have characterized the coordination of such ligands to ruthenium nanoparticles by solid-state NMR spectroscopy. [3] Surprisingly, the stabilization of MNPs with NHC ligands and, more specifically, the interaction between the metal surface and the NHC ligand, have rarely been studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…55 Platinum nanoparticles were synthesized by decomposition of [Pt(dba) 2 ] in THF at room temperature under 3 bar of H 2 and in the presence of variable amounts (0.2 or 0.5 equiv.) 55 Platinum nanoparticles were synthesized by decomposition of [Pt(dba) 2 ] in THF at room temperature under 3 bar of H 2 and in the presence of variable amounts (0.2 or 0.5 equiv.)…”
Section: View Article Onlinementioning
confidence: 99%